Factors That Can Be Predictors Of Carbon Emissions Disclosure - Arini Nur Khulil Jannah; I Made Narsa (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2021)
This research is to analyze the role of ISO 14001, performance environment index PROPER, environmental committee,and foreign diversity to carbon emissions disclosure in the plantation company that registered at the Indonesian stock exchange of 2013 to 2019. The data used was 77 companies. The testing of hypotheses usesmultiple linear regression with a minimal significanceof 5%. this research provesthat there is four a variable that has a significant result on the disclosure of the carbon emission in plantation company that is ISO 14001, performance environment index PROPER, environmental committee and Foreign diversity. Three variableshave no effect on the disclosure of carbon emissions that is age company, leverage,and return of equity. This research can be used stakeholder to see the company’s responsibilities through their environment to ensure there isno risk in the company’s future performance before reachingtheir investment decision.